2021
DOI: 10.11606/issn.2176-7262.rmrp.2021.172543
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à não adesão ao tratamento para tuberculose pulmonar

Abstract: Objetivo: analisar as evidências disponíveis na literatura sobre os fatores relacionados à não adesão ao tratamento diretamente observado por pessoas com tuberculose pulmonar. Métodos: trata-se de uma revisão integrativa da literatura. A busca ocorreu entre os meses de agosto de 2019 e maio de 2020, por acesso às bases de dados MEDLINE, LILACS, BDENF, BINACIS, IBECS, PUBMED, SCOPUS, e WEB OF SCIENCE, bem como via biblioteca virtual SCIELO, selecionando artigos publicados entre 2009 e 2019. Resultado: dos 1664 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
0
4
0
4
Order By: Relevance
“…[17,30,31] However, older age was also associated with factors known to improve their TB prognoses such as less IV drug use, HIV, and extra-pulmonary TB, and abandonment of treatment. [32][33][34] The distribution of risk factors for TB, therefore, can have variations across all adult age groups and identifying the high-risk profiles in the OA is important for prompt TB suspicion, diagnosis, and treatment initiation, in order to improve their prognosis. Regardless of a combination of risk and protective factors for TB in the OA in multivariable models, the highest threat to this age group was their higher odds of death of any cause during TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[17,30,31] However, older age was also associated with factors known to improve their TB prognoses such as less IV drug use, HIV, and extra-pulmonary TB, and abandonment of treatment. [32][33][34] The distribution of risk factors for TB, therefore, can have variations across all adult age groups and identifying the high-risk profiles in the OA is important for prompt TB suspicion, diagnosis, and treatment initiation, in order to improve their prognosis. Regardless of a combination of risk and protective factors for TB in the OA in multivariable models, the highest threat to this age group was their higher odds of death of any cause during TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Abandonment of treatment contributes to adverse outcomes but we found that the ELD are less likely to abandon TB treatment [30, 48, 49]. Interestingly, we found an inverse association between the number of TB contacts and odds of abandoning treatment in all age groups, or among ELD patients only.…”
Section: Discussionmentioning
confidence: 83%
“…[3][4][5][6]10 Others allude to the low level of knowledge about the disease, which can be related to socio-demographic factors, such as low education, low socioeconomic conditions, and difficulty of access, which influence the continuity of treatment, since the lower understanding of what the disease is can trigger affections such as fear, anxiety states, and other negative thoughts during the course of treatment for pulmonary TB. 7,[11][12][13][14] Of these studies, two were conducted in the North region of Brazil, [15][16][17][18] focusing on the obstacles to treatment, pointing out the little regional production, and reiterating the need for studies focused on this reality and its respective peculiarities.…”
Section: Introductionmentioning
confidence: 99%